STABILITY-INDICATING RP-HPLC METHOD FOR THE SIMULTANEOUS ESTIMATION OF ANTIRETROVIRAL DRUGS IN BULK AND TABLET FORMULATIONS - SUBHRANSHU PANDA,; SIRISHA GORANTLA, (The Bioscan, 2026)
A reliable, validated, and robust RP-HPLC method was established to evaluate Abacavir (ABV), Dolutegravir (DTV), and Lamivudine (LVD) in bulk and fixed-dose combination tablets. Chromatographic separation was achieved on a Sunfire C18 column (250 × 4.6 mm, 5 µm) using a mobile phase of 0.01 N ammonium acetate:acetonitrile (60:40 v/v) at a flow rate of 1.0 mL/min, with detection at 257 nm. The column temperature was maintained at 30°C and the run time was 6 min. The method was linear over 0-180 µg/mL for ABV, 0-15 µg/mL for DTV, and 0-90 µg/mL for LVD with correlation coefficients (R²) of 0.9993, 0.9998, and 0.9998, respectively. Accuracy was within 98.15-101.35% and precision showed %RSD < 1%. The LOD/LOQ values were 0.746/2.261 µg/mL for ABV, 0.057/0.172 µg/mL for DTV, and 0.293/0.888 µg/mL for LVD. Forced degradation showed maximum degradation of 6.83% (ABV), 8.01% (DTV), and 5.28% (LVD), confirming specificity and suitability for stability and routine QC. Keywords Abacavir, Dolutegravir, Lamivudine, RP-HPLC, method validation, stability-indicating, forced degradation, ICH Q2(R1)